The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12911-015-0195-x
|View full text |Cite
|
Sign up to set email alerts
|

Are family physicians comprehensively using electronic medical records such that the data can be used for secondary purposes? A Canadian perspective

Abstract: BackgroundWith the introduction and implementation of a variety of government programs and policies to encourage adoption of electronic medical records (EMRs), EMRs are being increasingly adopted in North America. We sought to evaluate the completeness of a variety of EMR fields to determine if family physicians were comprehensively using their EMRs and the suitability of use of the data for secondary purposes in Ontario, Canada.MethodsWe examined EMR data from a convenience sample of family physicians distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 30 publications
0
56
1
Order By: Relevance
“…At the time of the study the data in EMRALD were contributed by 83 primary care physicians who had been using their EMR for at least 2 years and whose data met quality and completeness standards. 3 EMRALD patients and physicians are similar to all Ontario patients and physicians for most characteristics. 3 A random sample of 7500 adult patients aged 20 years or older as of December 31, 2010 was drawn from 73,014 adult patients of EMRALD physicians.…”
Section: Methodsmentioning
confidence: 76%
“…At the time of the study the data in EMRALD were contributed by 83 primary care physicians who had been using their EMR for at least 2 years and whose data met quality and completeness standards. 3 EMRALD patients and physicians are similar to all Ontario patients and physicians for most characteristics. 3 A random sample of 7500 adult patients aged 20 years or older as of December 31, 2010 was drawn from 73,014 adult patients of EMRALD physicians.…”
Section: Methodsmentioning
confidence: 76%
“…The physician level factor is years the physician has been using EMRs. It was previously shown that it takes approximately 2 years for a physician to adequately populate the EMR records for their practice 12. Patient level factors examined were age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…However, research networks, such as the Canadian Primary Care Sentinel Surveillance Network11 and the Electronic Medical Record Administrative data Linked Database (EMRALD)12 in Canada, and the Electronic Pediatric Research in Office Settings (ePROS) network in the United States, have attempted to move EMR research forward by acting as an intermediary between primary care providers and researchers. Multiple studies have been published using these data sources to estimate both child and adult obesity rates 13 – 15.…”
Section: Introductionmentioning
confidence: 99%
“…The representativeness of EMRALD patients and physicians, in addition to the quality and comprehensiveness of EMRALD data, has been previously found to be generally reflective of the Ontario population. 28,29 Young adults and people with lower socioeconomic status are slightly under represented in EMRALD compared with the general Ontario population; however, this is likely characteristic of the types of people that see a physician and not anything specific to EMRALD patients. Relative to all Ontario physicians, EMRALD physicians practise more in rural locations and fewer are foreign-trained physicians.…”
Section: Measurement Of Quality Indicatorsmentioning
confidence: 98%